To Evaluate The Comparative Study Of Navayas Lauha With Controlled Known Drug In The Management Of Pandu Roga W.S.R. To Iron Deficiency Anaemia - Gutakar, Sneha; Bhadoria, Anil (International Research Journal of Ayurveda & Yoga, 2021)
Background- In this 21st century, life style changes very rapidly. Now there is competition in every field so most of people have lot of stress. As life style is changing in the society, their diet habits are also changing very rapidly. Now a day’s people take Fast food regularly, moreover they show negligence in taking care of their health. As a result of this, people are suffering from various diseases, among these diseases Pandu Roga is very common disease seen especially in the developing countries like India. On the basis of information from published and unpublished sources and the hemoglobin cut –off points recommended by WHO scientific group, it is estimated that about 30% of the world’s population of 5000 million people are Anemic. Aim- To evaluate the effect of an ayurvedic formulation Navayas Lauha in the management of pandu roga on clinical parameters Materials and Methods- Total 30 patients of Pandu were selected for the present study from the OPD and IPD of Jammu Institute of Ayurveda and Research hospital, Jammu. They were treated in 2 groups; • Group A: 15 patients were included in this group and were given Navayas Lauha 200mg OD orally. • Group B: 15 patients were included in this group and were given dried Ferrous Sulphate 150mg OD orally. Result- overall percentage of improvement in both the groups on different clinical parameters, it was noticed that there was 53.15% improvement in Group A, 39.52% improvement in Group B. Conclusion- The study revealed that the selected management was better potential effects on Pandu Roga with the added advantage of being free from Side Effects